Influence of Physical Spray Characteristics and Presence of Glyphosate in Enhancing the Performance of Metsulfuron-Methyl Against Woody Borreria (Diodia Ocimifolia) - Ooi, Kok Eng (1999)
Influence of physical spray characteristics (carrier volume, herbicide dosage and surfactant) and presence of glyphosate on the performance of metsulfuron-methyl against woody borreria (Diodia ocimifolia) was studied in the glass house. The activity of metsulfuron-methyl on Diodia ocimifolia was influenced by herbicide dosage, carrier volume, surfactant and the interaction of these factors. The performance of metsulfuron-methyl increased as herbicide dosage increased irrespective of carrier volume. The results indicated that 30 g/ha metsulfuron-methyl was required for effective control of Diodia. A significant decrease in performance of metsulfuron-methyl was observed as the carrier volume increased from 200 to 600 L ha-1. The presence of surfactant increased the activity of metsulfuron-methyl against Diodia at carrier volu mes of 400 and 600 L ha-1 • However, the results did not indicate loss in herbicide performance for carrier volume less than 200 L ha-1 in the absence and presence of surfactant. These observed responses were further illustrated using models obtained by linear regression analysis. Metsulfuron-methyl applied to D. ocimifolia at both growth stages caused seedling mortal ity and reduced seed production. Diodia ocimifolia was more susceptibie at the vegetative stage compared to the flowering stage. Shoot tip growth was arrested at low dosage of 3.75 g/ha. However, metsulfuron-methyl dosage required for complete kill of Diodia seedlings was 15 g/ha at the vegetative stage and 30 g/ha at the flowering stage. Metsulfuron-methyl applied at the flowering stage caused flower abscission but did not inhibit germination of seeds collected from treated plants. Metsulfuron-methyl and glyphosate mixtures at all ratios were more effective than the herbicides used alone. At low rates of metsulfuron-methyl (3.75 and 15 g/ha), the response in the presence of glyphosate (135 and 540 g/ha) with and without surfactant (1:36 mixtures) was synergistic or additive. However, in the 1:72 mixture the interaction response became additive. The same response was obtained with the 1:18 mixture. The results indicate that the appropriate combination for optimum performance is the 1:36 mixture both in the presence and absence of surfactant.